2007
DOI: 10.1136/bjo.2007.116897
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of multi-use ophthalmic solutions in Kenya

Abstract: Background/aims: Contaminated ophthalmic solutions represent a potential cause of avoidable ocular infection. This study aimed to determine the magnitude and pattern of microbial contamination of multi-dose ocular solutions at the Department of Ophthalmology, University of Nairobi, at the Kenyatta National Hospital, Kenya. Methods: 101 vials were obtained for microbial examination after an average use of 2 weeks. The dropper tip and the residual eye drop were examined for contamination. The specimens were cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(92 citation statements)
references
References 11 publications
8
82
2
Order By: Relevance
“…Most reported studies have focussed patient-used preparations and high prevalence of microbial contaminations in these preparations have been reported. [7,8] Although most of these studies have attributed these contaminations to the use of the eye drops, it is doubtful if these assertions have any scientific basis since the microbial quality of the original eye drop products are largely assumed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most reported studies have focussed patient-used preparations and high prevalence of microbial contaminations in these preparations have been reported. [7,8] Although most of these studies have attributed these contaminations to the use of the eye drops, it is doubtful if these assertions have any scientific basis since the microbial quality of the original eye drop products are largely assumed.…”
Section: Discussionmentioning
confidence: 98%
“…[7] Eye drops were opened and exposed to the atmosphere by placing them on the open shelves in the laboratory. Samples were taken at 0, 2, 4, 8, 24, 48, and 72 h, then 7, 14, 28, and 56 days.…”
Section: Investigation Of Contamination By the Airmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The dropper tip is more often contaminated than the residual solution in the bottle and the organisms cultured tend to be the normal commensal flora of the eye. 4 These are unlikely to cause problems but there is a risk of infection. 5 These two facts have led to the development of individual containers, which can be used on one patient as a single dose, obviating the need for preservatives, and reducing to zero the risk of cross-contamination by microorganisms commonly found on the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown contamination of multiuse ophthalmic solutions and their applicators. [1][2][3] There is, however, little evidence that accurately assesses the safety of using Minims vials for multiple applications.…”
Section: Introductionmentioning
confidence: 99%